Age-Related Decline in Anticipatory Motor Planning and Its Relation to Cognitive and Motor Skill Proficiency - Stöckel, Tino; Wunsch, Kathrin; Hughes, Charmayne M. L. (Frontiers in Aging Neuroscience, 2017)
Anticipatory motor planning abilities mature as children grow older, develop throughout childhood and are likely to be stable till the late sixties. In the seventh decade of life, motor planning performance dramatically declines, with anticipatory motor planning abilities falling to levels of those exhibited by children. At present, the processes enabling successful anticipatory motor planning in general, as do the cognitive processes mediating these age-related changes remain elusive. Thus, the aim of the present study was a) to identify cognitive and motor functions that are most affected by normal ageing and b) to elucidate key (cognitive and motor) factors that are critical for successful motor planning performance in young (n = 40, mean age = 23.1 ± 2.6 years) and older adults (n = 37, mean age = 73.5 ± 7.1 years). Results indicate that normal aging is associated with a marked decline in all aspects of cognitive and motor functioning tested. However, age-related declines were more apparent for fine motor dexterity, processing speed and cognitive flexibility. Furthermore, up to 64% of the variance in motor planning performance across age groups could be explained by the cognitive functions processing speed, response planning and cognitive flexibility. It can be postulated that anticipatory motor planning abilities are strongly influenced by cognitive control processes, which seem to be key mechanisms to compensate for age-related decline. These findings support the general therapeutic and preventive value of cognitive-motor training programs to reduce adverse effects associated with high age.